Managing and training for virtual teams in India - Holtbrügge, Dirk; Schillo, Katrin; Rogers, Helen; Friedmann, Carina (Team Performance Management, 2011)
Purpose: The purpose of this study is to investigate the current and potential use of virtual teams in the Indian context. Design/methodology/approach: The use of virtual styles and strategies was assessed through a series of questionnaires, focusing on managerial aspects. The sample consisted of companies and individuals from Europe, who work on virtual assignments. The results were analysed, paying particular attention to the actual usage and potential future usage of virtual assignments. Findings: It was found that a disparity between the actual and the potential use of virtual delegates exists. Furthermore, the increasing use of virtual delegates requires tailored intercultural training, which meets the specific demands of these delegates and the requirements of virtual teamwork. The paper goes on to discuss how traditional training can be adapted for the training of virtual assignees. Originality/value: The findings have implications for both academics and practitioners, as they indicate that there is significant potential for further growth in the use of virtual assignments. In particular, the paper highlights the need for specific, dedicated training in virtual assignments, as this has a substantial impact on their success. © Emerald Group Publishing Limited.
WiSo-Import:2015-03-26:889
Keywords: Transformation